Asproinocybe hongyaniae sp. nov. (Agaricales, Basidiomycota) in Thailand - Lv, Tong; Wang, Shuai; Wu, Xiaoqu; Chen, Dechao; Ao, Chengce; Luo, Hongmei; Li, Erxian; Tang, Songming; Li, Shuhong (Phytotaxa, 2024)
Asproinocybe hongyaniae, a new species discovered in northern Thailand, is described, illustrated, and compared with phylogenetically related and morphologically similar species. This new species is characterized by the medium grey to olive grey pileus, light violet to violet blue lamellae, oblong and colourless basidiospores (5.8–8.5 × 4.5–6.3 μm), narrowly clavate pleurocystidia and cheilocystidia. Molecular analyses employing the internal transcribed spacer (ITS) and large subunit (nrLSU) of nuclear ribosomal DNA sequences strongly supported the new species. An updated key is also provided to assist in identifying all ten Asproinocybe species in the genus. The genus Asproinocybe is the first report in Thailand.